Sharing Session untuk Komunitas Sane Step dengan Model Knowledge Creation Nonaka (Universitas Negeri Jakarta, 2019)
The research is aimed to result sharing session design for Sane Step Community. This sharing session design has been developed by the needs of participants and addressed for Sane Step organizing team. This sharing session design is equipped with the design foundation, outline of sharing session process and outline of material content. The research refers to Knowledge Creation model by Nonaka, which start from Enlarging Individual Knowledge, Sharing Tacit Knowlegde, Conceptualization-Crystalitation, and Justification. The research was conducted at SCTV Tower, 19th floor, Senayan, South Jakarta, with 10 respondens. The data collected by interview, distribution of questionnaires and rubric assessment. The result showed 80% of positive respond from the participants. This research was claimed in good criteria. The participants state the sharing session topic able to answer their needed, and presented by the speaker in a good way using interactive media and method. The implication from this research is Sane Step Community capable to held sharing session much better based on needs of participants.The research is aimed to result sharing session design for Sane Step Community. This sharing session design has been developed by the needs of participants and addressed for Sane Step organizing team. This sharing session design is equipped with the design foundation, outline of sharing session process and outline of material content. The research refers to Knowledge Creation model by Nonaka, which start from Enlarging Individual Knowledge, Sharing Tacit Knowlegde, Conceptualization-Crystalitation, and Justification. The research was conducted at SCTV Tower, 19th floor, Senayan, South Jakarta, with 10 respondens. The data collected by interview, distribution of questionnaires and rubric assessment. The result showed 80% of positive respond from the participants. This research was claimed in good criteria. The participants state the sharing session topic able to answer their needed, and presented by the speaker in a good way using interactive media and method. The implication from this research is Sane Step Community capable to held sharing session much better based on needs of participants.